Tragic heroines in ancient Greek drama - Roisman, Hanna, 1948- (London ; New York, NY)
x, 314 sayfa
Keywords: “The heroines of Greek tragedy presented in the plays by Aeschylus, Sophocles and Euripides have long captivated audiences and critics. In this volume each of the eleven chapters discusses one of the heroines: Clytemnestra, Hecuba, Medea, Iphigenia, Alcestis, Antigone Electra, Deianeira, Phaedra, Creusa and Helen. The book focuses on characterisation and the motivations of the women, as well as on those of the male playwrights, and offers multiple viewpoints and critiques that enable readers to understand the context of each play and form their own views. Four core themes bridge the depictions of the heroines: the socio-political dynamic of ancient Greek expectations of women and their roles in society, the conflict of masculinity versus femininity, the alternation of defiance and submission, and the interplay between deceit and rhetoric. Each chapter offers clear descriptions of plot and mythical background, and builds on the text of the plays to enable reflections on language and performance. All technical terms are explained and key topics or references are pulled out into box features that provide further background information. Discussion points at the ends of chapters enable readers to explore various topics more deeply“ --